2021
DOI: 10.1186/s43065-021-00026-1
|View full text |Cite
|
Sign up to set email alerts
|

Coastal green infrastructure to mitigate coastal squeeze

Abstract: Infrastructure is necessary to protect and provide the goods and services required by humans. As coastal green infrastructure (CGI) aims to respect and work with natural processes, it is a feasible response to mitigate or avoid the consequences of coastal squeeze. The concept of CGI is receiving increased attention of late due to the challenges facing us, such as climate change, population growth and the overexploitation of natural resources on the coast. Terms which may be applied to encourage the constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 56 publications
0
17
0
13
Order By: Relevance
“…However, Pereira et al [50] showed that the main anthropic impacts have a direct relationship with infrastructures, such as breakwaters and seawalls. Traditional engineering designs for coastal protection structures often modify the dynamics of the ecosystems, possibly resulting in their isolation, and therefore in a reduced ability to provide ecosystem services [24], perhaps even reaching a point of no return at which coastal ecosystems can no longer be restored [51]. The more interventions there are on a beach, the more necessary it is to perform morphological measurements at a fine spatial scale (metres) and to quantify anthropic indices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Pereira et al [50] showed that the main anthropic impacts have a direct relationship with infrastructures, such as breakwaters and seawalls. Traditional engineering designs for coastal protection structures often modify the dynamics of the ecosystems, possibly resulting in their isolation, and therefore in a reduced ability to provide ecosystem services [24], perhaps even reaching a point of no return at which coastal ecosystems can no longer be restored [51]. The more interventions there are on a beach, the more necessary it is to perform morphological measurements at a fine spatial scale (metres) and to quantify anthropic indices.…”
Section: Discussionmentioning
confidence: 99%
“…Fine temporal and spatial scale measurements give an accurate morphological analysis of this coastline, which can provide important information for decision-making in this remote area [10]. On the other hand, although coastal morphodynamics are mainly controlled by the interaction of natural processes, coastal protection structures do modify some coastal processes [24]. Determining the anthropogenic impact of such structures makes it possible to evaluate how much they influence the evolution of the coastline.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the new beachscape must face the social perceptions and acceptance surrounding the implementation of these projects. Failure to comply with environmental regulations or encourage the population's involvement (stakeholders, staff, or visitors) is of great importance for the project's success [93]. For instance, [94] explored the perception of beachgoers to new management strategies aimed at protecting threatened bird species on urban beaches.…”
Section: Caveats Of the Proposalmentioning
confidence: 99%
“…In terms of coastal risk management, when storms are likely to damage human infrastructure and result in the loss of human lives, the above-mentioned biogeomorphological system generated through the dynamic interaction between plants and dunes, becomes highly relevant. This is especially true for coastal green infrastructure solutions whose premise is to protect exposed human interests from ocean hazards, and potentially from sea-level rise, by working with natural processes (Temmerman et al, 2013;Spalding et al, 2014;Chávez et al, 2021). Coastal dunes are often the first natural terrestrial defense against storm impact.…”
Section: Introductionmentioning
confidence: 99%